Formulation and in-vitro antioxidant evaluation of α-mangostin, piperin, curcumin in oral patch and their combination - Suharyani, Ine Suharyani; Mardianingrum, Richa; Falya, Yuniarti; Pratama, Rizki; Mas'ud, Ibnu; Daruwati, Isti (Universitas Ahmad Dahlan, 2025)
Natural antioxidants have been developed in various formulations as alternatives to reduce the side effects associated with synthetic antioxidants. α-Mangostin exhibits strong antioxidant properties, although its behavior in combination with other herbal compounds remains unclear. The aim of this study was to formulate a combination of α-M, piperine, and curcumin into an oral patch and to evaluate the antioxidant properties of α-M when combined with piperine and curcumin, both known natural antioxidants. The oral patches were prepared by incorporating the active compounds (α-mangostin, piperine, and curcumin) into a matrix of hydroxypropyl methylcellulose (HPMC), gelatin, and chitosan. Glycerin was added as a plasticizer. Organoleptic assessment, along with evaluations of pH, weight, folding endurance, and moisture absorption capacity, confirmed the successful formulation of α-mangostin (MP), piperine (PP), curcumin (CP), and combination (MPCP) patches as oral delivery systems. All patches maintained a pH above 5.5. The thicknesses of MP, PP, CP, and MPCP were measured at 0.14 ± 0.02 mm, 0.17 ± 0.01 mm, 0.15 ± 0.02 mm, 0.11 ± 0.01 mm, and 0.16 ± 0.02 mm, respectively. The combination of these natural compounds enhanced folding endurance compared to the individual curcumin and piperine patches, while slightly reducing antioxidant activity. The co-formulation of α-mangostin, piperine, and curcumin into a single oral patch demonstrated a modest decline in antioxidant capacity. This study aimed to assess the impact of combining multiple antioxidant-rich natural compounds within a single delivery system.